Accuracy and fairness – Siamese twins? - Thomas Weigend (Quaestio Facti)
The author agrees with Sarah Summers’ view that a criminal judgment in a system of fair justice should be substantively accurate and at the same time should be the result of a fair process. The author argues, however, for keeping these two requirements apart because they are linked to different goals and may in individual cases conflict with each other.